Story Method in Applying Islamic Religious Education Values in Early Childhood Education Students - Misra, Misra; Trinova, Zulvia; Nasution, Riskha Hanifa; Mayuni, Windri (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to describe the story method and its implications in applying Islamic Religious Education values in early childhood. This is a descriptive qualitative study with data collected through observation, interviews, and documentation. This study analyzed data through data reduction, data presentation, and drawing conclusions. The findings revealed that forming faith, worship, and morals at an early age in learning can be accomplished through the use of the story method, in which the teacher reads directly to students a unique and exciting storybook containing the value of Islamic religious education. Then, the teacher illustrates what is told to the students. It is also enriched with good habits through daily routine activities, exemplary teachers, discipline, and applying the values of faith, worship, and morals in life so that students can understand the materialexplained by the teacher. Concluded, following the implementation of the story method at PAUD Durian Ajung Padang Pariaman, students have applied good morals when entering classrooms by reciting prayers taught by the teacher and performing greetings. Those activities have become habits performed daily.